Dos flooding attack control in information-centric networks - Rao T, Srinivasa; G, Harsha; V, Kiran; Kumar K, Hemanth (International Journal of Engineering and Technology, 2017)
ICN (Information-centric networking) is a modern networking standard that mainly works only on the content extraction from a network without taking into case about the storage location or how the content is represented. In ICN providing security for the content is more important. Here we don’t concentrate on protecting path. In order to fulfil the security goals in the new standard, it is very decisive to have a clear complete comprehension about ICN attacks and their brief allocation and the solutions. In this paper we in brief explain the attacks which effect the ICN network and other related attacks which have an impact on ICN. Attacks in ICN are divided to four categories, routing attacks, Naming attacks, Caching attacks, and other various related attacks. There are lot of solutions which are accessible. The main moto in ICN is to protect data which is very hard to achieve. So we develop a dynamic host based IP address scheme including certain snort rules which detect attacker and distinguish them in the clients and secure server from resource exhaustion. Our main center we deal with is on availability, and privacy.